Osmotic and apparent molar properties of binary mixtures alcohol+1-butyl-3-methylimidazolium trifluoromethanesulfonate ionic liquid - Emilio J. González (2013)
In this work, physical properties (densities and speeds of sound) for the binary systems {1-propanol, or 2-propanol, or 1-butanol, or 2-butanol, or 1-pentanol + 1-butyl-3-methylimidazolium trifluoromethanesulfonate} were experimentally measured from T = (293.15 to 323.15) K and at atmospheric pressure. These data were used to calculate the apparent molar volume and apparent molar isentropic compression which were fitted to a Redlich-Meyer type equation. This fit was used to obtain the corresponding apparent molar properties at infinite dilution. On the other hand, the osmotic and activity coefficients and vapor pressures of these binary mixtures were also determined at T = 323.15 K using the vapor pressure osmometry technique. The Extended Pitzer model of Archer was employed to correlate the experimental osmotic coefficients. From the parameters obtained in the correlation, the mean molal activity coefficients and the excess Gibbs free energy for the studied mixtures were calculated.